Multifunctional and anti-migration plasticizers based on bio-based phenol-functionalized liquid 1, 2-polybutadiene. (15th January 2023) - Gao, Wenke; Zhang, Wenjing; Liu, Jinhui; Hua, Jing
Abstract: With the increasing demands for environmental friendliness, bio-based additives in rubber materials have attracted extensive research attention from the academy and industry. However, the low molecular weight and high polarity are detrimental to mixing compatibility with rubber materials. In this work, we prepare a phenol-functionalized 1, 2-PB (1, 2-PB- g -CA) by grafting bio-based cardanol onto 1, 2-polybutadiene rubber (1, 2-PB) based on the olefin metathesis. The 1, 2-PB- g -CA demonstrate a controlled number average molecular weight from 7 × 10 3 to 4 × 10 4 and tuned functionality from 0% to 20%. The open reaction system exhibited a higher functionality due to the removal of small molecules. The 1, 2-PB- g -CA was used as a plasticizer for silica filled styrene-butadiene rubber (SBR). The enhanced interfacial interaction between phenolic hydroxyl groups of cardanol and the silanol groups of silica significantly increased the compatibility of silica and rubber matrix. Compared with the common paraffinic oil, the obtained SBR/silica compounds were afforded low rolling resistance, high wet grip, and low heat build-up. Moreover, the 1, 2-PB- g -CA showed better anti-migration properties. Therefore, our preparation method of bio-based modified liquid rubber has broad application prospects in high-performance "green tire." Highlights: 1, 2-PB- g -CA was prepared based on olefin metathesis reaction. The Mn and functionality of the 1, 2-PB- g -CA could be adjusted in a wide range. 1, 2-PB-g-CA can improve the blend compatibility between SBR and silica. 1, 2-PB- g -CA has the characteristics of strong processability and anti-migration.